Law, Marxism and Method - Paul O'Connell (tripleC: Communication, Capitalism & Critique)
Law is crucial to the maintenance and reproduction of capitalism. While Marx never produced a comprehensive theory of law, state and rights, there is much in his work, and in the broader Marxist tradition, that can help us understand the nature and role of law in contemporary capitalism. This paper sketches out some of the key resources from within the Marxist tradition that can assist us in developing Marxist understandings of law, state and rights today. Specifically, the focus is on the question of method, drawing out three key strands from Marx's own work: (i) the importance of dialectical materialist analysis; (ii) the historically specific and transitory nature of capitalism and (iii) the centrality of class antagonism and class struggle. The argument advanced here, in sum, is that Marxist explanations of law, state and rights should foreground these analytical reference points, in order to make the role of law intelligible, and to begin to sketch how movements for fundamental social change might understand and engage with the law.